Adjectives and adjectival present participles in the translation of advertising texts from English to Polish - Piecychna, Beata (Papers in Linguistics, 2020)
The main aim of this article is to discuss certain tendencies in advertising translation from English to Polish in regard to adjectives and adjectival present participles in a product description used in the beauty industry. More specifically, the author’s purpose is to verify whether the way of translating selected units of analysis corresponds to general rules of creating effective marketing texts which were designed by experts within the field of sales and marketing as well as by linguists. The study is based on a description of Oriflame’s Blue Wonders perfume and its translation into Polish. The analysis shows that the adjectival forms employed in the source text which were crucial from the perspective of the specificity of a marketing text were either omitted or translated inadequately when it comes to the purpose of the product description.